Pharmaceutical policies and regulations of oral antiviral drugs for treatment of hepatitis C in Egypt-case study - Mahmoud H. Teaima; Adi Al-Nuseirat; Dalia Abouhussein; Osama A. Badary; Mohamed A. El-Nabarawi (Taylor & Francis Group, 2021)
Background There are limited studies on the role of efficient regulatory mechanisms in facilitating greater access to Hepatitis C virus (HCV) treatment. Evidence to support the importance of effective pharmaceutical policies and regulations in improving access to oral viral drugs towards the elimination of HCV is needed. This study aims to explore the adequacy of the implemented pharmaceutical policies and regulations in Egypt and their role to improve the availability and affordability of direct-acting antivirals (DAAs) to achieve universal access to the treatment of HCV. Methods The study adopts a qualitative methodology using desk review of regulatory and legislative information, literature review, and semi-structured interviews with key experts from the concerned governmental regulatory agencies, pharmaceutical industries, academic organizations, professional associations, civil society organizations, and clinicians who are working in researching treatments for hepatitis C. Findings The common DAAs available in the market are Daclatasvir, Sofosbuvir, and Sofosbuvir-based direct-acting antiviral combinations. Fast-track medicines registration pathway for marketing authorization of DAAs is used to reduce market access time frames. The pricing policies are supplemented using price negotiation to set up affordable prices that led to a reasonable price for DAAs. Using Trade-Related Aspects of Intellectual Property Rights (TRIPs) flexibility and local production of quality generics DAAs at lower prices. In addition, political will and collaboration between the government, civil society, and pharmaceutical companies improved patients' access to affordable DAAs and succeeding hepatitis C treatment in Egypt. Conclusions The study findings indicated that the implemented pharmaceutical policies and regulations have an immense role in enhancing access to medicines towards the elimination of hepatitis C in Egypt.